AN ALTERNATIVE METHOD OF INCREASING THE TRANSMISSION PER- FORMANCE OF A CONVENTIONAL 110 kV CABLE LINE - Klimenta, Dardan; Tasić, Dragan; Jevtić, Miroljub (Journal of Energy Technology, 2024)
The purpose of this paper is to show that a significant increase in the ampacity of a 110 kV underground cable line is achievable, if a hydronic asphalt pavement system is applied along the entire line, and if the cable trench is completely filled with high thermal conductivity bedding in order to improve the conduction of heat between the line and the surface of the earth. In such a way, it would be possible to simultaneously collect and then store heat from the sun and cable line. The mutual thermal effects between the 110 kV cable line and the hydronic asphalt pavement, in the presence of solar radiation, wind-driven convection and heat emission along the earth surface, are simulated using FEM-based models for the most unfavourable summer conditions and the most common winter conditions. An adequate experimental background is also provided based on the existing measurements relevant to the thermal analysis performed. It was found that, compared to the associated base cases, the cable ampacity can be increased up to 92.3% for the most unfavourable summer conditions, and up to 60.3% for the most common winter conditions.